Research of a 1st-century BC shipwreck off Cape Letavica on the island of Pag (In situ, 2024)
The site of sinking of the ancient ship near Cape Letavica, not far from Šimuni on the island of Pag, was found during a tourist diving trip in 2018 by Vedran Dorušić, owner of the Foka Diving Center, located in Camping Village Šimuni. The site comprises about 400 wine amphorae of the Lamboglia 2 type dating to the 1st century BC which lie on the slope of the seabed, outlining the shape of a sunken ship. In 2022, the fourth research campaign was carried out. The excavation took place in three different sectors. The north-eastern end of the site was recleaned, in order to completely clean and document the two previously discovered lead stocks of Roman anchors. One trench was placed over the upper edge of the northeastern part of the site, in order to check whether there are preserved parts of the wooden ship structure under the sediment. The second trench was placed under the lower edge of the southwestern part of the site, where the ship's galley was assumed to be. The assumed finds were confirmed in both trenches.
Keywords: Pag; cape Letavica; shipwreck; Antiquity